DAKWAH MELALUI KEARIFAN LOKAL SEDEKAH BUMI DI DESA LINGGOASRI - Fatmawati; Soffiyana Dwi Jupriyanti; Nelsa Reykhana Agustina F; Qomariyah (Jurnal Komunikasi dan Media, 2025)
Preaching through local wisdom of earthly charity is a tradition that integrates religious values and cultural traditions, which is key to building effective relationships with the community. This study focuses on how this strategy of preaching through earth-wise local wisdom in Linggoasri village works. Methodology This study used qualitative method with data collection being done in the form of observation and interviews. The results of the research show that the strategy of Sedekah Bumi or legenonan in Linggoasri is with a cultural and socio-cultural approach as a form of gratitude to God, not only the Muslim community participates, but the Hindu, Buddhist and Christian community also participate actively in the activities of sedekah bumi. Thus, earthly charity can be an effective preaching in Linggoasri in its various diversities.